2010
DOI: 10.2323/jgam.56.11
|View full text |Cite
|
Sign up to set email alerts
|

Chromate reductase activity in Streptomyces sp. MC1

Abstract: Biological transformation of Cr(VI) to Cr(III) by enzymatic reduction may provide a less costly and more environmentally friendly approach to remediation. In a previous report a Cr(VI) resistant actinomycete strain, Streptomyces sp. MC1, was able to reduce Cr(VI) present in a synthetic medium, soil extract and soil samples. This is the first time optimal conditions such as pH, temperature, growth phase and electron donor have been elucidated in vitro for Cr(VI) reduction by a streptomycete. Chromate reductase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
34
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 41 publications
0
34
0
Order By: Relevance
“…In turn, biological transformation of Cr(VI) to Cr (III) by enzymatic reduction has been recognized as a means of chromium decontamination from effluents (Laxman and More 2002;Polti et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In turn, biological transformation of Cr(VI) to Cr (III) by enzymatic reduction has been recognized as a means of chromium decontamination from effluents (Laxman and More 2002;Polti et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have indicated a correlation between multiple antibiotic Science Publications AJBB resistance and heavy metal resistance (Bahig et al, 2008;Spain, 2003). Heavy metal resistance together with metabolic diversity and specific growth characteristics of actinomycetes, such as, mycelium formation and relatively rapid colonization of selective substrates indicate them as suitable agents for bioremediation (Polti et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Cr(VI) is highly water soluble and more mobile, thus spreads easily beyond the site of initial contamination, while Cr(III) is relatively inert, less mobile, less bioavailable and easily adsorbed on mineral surfaces. Besides, hexavalent chromium compounds are approximately 100 fold more toxic and 1000 fold more mutagenic than trivalent chromium (Polti et al, 2010;2007). Chromium containing effluents from industries like leather tanning, chrome-plating, wood preservation, dye industry are released directly or indirectly into natural water resources, mostly without proper treatment which renders chromium associated environmental pollution, a major concern.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations